2021
DOI: 10.1099/acmi.0.000249
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carriage rates and serotype distribution of Streptococcus pneumoniae among school children with acute otitis media in Central Java, Indonesia

Abstract: Streptococcus pneumoniae is a common bacterial pathogen that causes acute otitis media (AOM) in children. In this study, we investigated nasopharyngeal carriage rates and serotype distributions of S. pneumoniae among school children with AOM in Banyumas Regency, Central Java, Indonesia, from 2018 to 2019. Nasopharyngeal swab specimens and demographic data were collected from 122 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Previously, we have reported that 73% and 69.7% of S. pneumoniae and H. influenzae were identified from the same set of nasopharyngeal specimens respectively. 7 , 8 We analysis further regarding the co-infection of viruses and bacteria of S. pneumoniae and H. influenzae . We found that 62.2% (23/37) of nasopharyngeal swab samples that detected positive for viruses were also detected positive for both S. pneumoniae and H. influenzae bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have reported that 73% and 69.7% of S. pneumoniae and H. influenzae were identified from the same set of nasopharyngeal specimens respectively. 7 , 8 We analysis further regarding the co-infection of viruses and bacteria of S. pneumoniae and H. influenzae . We found that 62.2% (23/37) of nasopharyngeal swab samples that detected positive for viruses were also detected positive for both S. pneumoniae and H. influenzae bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the specimens were transported to the laboratory, vortexed, and stored at −80°C within 4 hours after collection. 7 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Israel, carriage rates tested on ages between 2 and 24 months was shown to increase with age from 2 months with 26% carriage rate to 62% at age of 24 months [23]. In a recent study about carriage of the pneumococcus in Indonesia showed high carriage rate of 73% in school children with acute otitis media (AOM) [24]. Dominant serotypes of the school children were 23A (11 %), 6A/6B (10 %), 3 (8 %), 14 (7 %), 6C/6D (7 %), 11A/11D (6 %), 15B/15C Other study in south Italy on healthy children aged 1-7 years attending day-care centers and schools showed nasopharyngeal colonization rate of Streptococcus pneumoniae to be 18.29%.…”
Section: Resultsmentioning
confidence: 99%
“…4015/KEPK/FK/2018.3574. Among school children screened for AOM infection, 166 children were diagnosed with positive cases of AOM [ 9 , 10 ]. However, only 122 nasopharyngeal (NP) swab specimens were available for the present study.…”
Section: Methodsmentioning
confidence: 99%